Answer
Verified
430.5k+ views
Hint:
Here, we will first rationalize the given numerator and try to simplify it further so that we can apply the u-substitution method. Solving this further and using the formula of integration of ${x^n}$, we will be able to find the required answer. Integration is defined as the summation of all the discrete data.
Formula Used:
We will use the following formulas:
1) $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$
2) ${\sin ^2}x + {\cos ^2}x = 1$
3) $\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}}} + C$
Complete step by step solution:
The given integral function is $\int {\left( {\dfrac{{\sqrt {1 - \cos x} }}{2}} \right)} dx$.
This can also be written as: $\dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx$
Now, we will do the rationalization by multiplying and dividing by $\sqrt {1 + \cos x} $
Hence, we get,
$\dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {1 - \cos x} \times \sqrt {1 + \cos x} }}{{\sqrt {1 + \cos x} }}} dx$
Using the identity $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$ in the numerator, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {1 - {{\cos }^2}x} }}{{\sqrt {1 + \cos x} }}} dx$
Also, ${\sin ^2}x + {\cos ^2}x = 1$
Or $1 - {\cos ^2}x = {\sin ^2}x$
Thus, substituting this value in the numerator,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {{{\sin }^2}x} }}{{\sqrt {1 + \cos x} }}} dx = \dfrac{1}{2}\int {\dfrac{{\sin x}}{{\sqrt {1 + \cos x} }}} dx$…………………..$\left( 1 \right)$
Now, by u-substitution, let $1 + \cos x = t$
Differentiating both sides, with respect to $x$, we get,
$ - \sin xdx = dt$
Or $\sin xdx = - dt$
Substituting this in $\left( 1 \right)$, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\int {\dfrac{1}{{\sqrt t }}} dt$
This can also be written as:
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\int {{t^{ - \dfrac{1}{2}}}} dt$
We know that, $\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}}} + C$
Hence, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\left( {\dfrac{{{t^{ - \dfrac{1}{2} + 1}}}}{{ - \dfrac{1}{2} + 1}}} \right) + C = - \dfrac{1}{2}\left( {\dfrac{{{t^{\dfrac{1}{2}}}}}{{\dfrac{1}{2}}}} \right) + C$
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - 2 \times \dfrac{1}{2}\left( {{t^{\dfrac{1}{2}}}} \right) + C = - \sqrt t + C$
But we know that, $1 + \cos x = t$
Hence,
$\int {\left( {\dfrac{{\sqrt {1 - \cos x} }}{2}} \right)} dx = - \sqrt {1 + \cos x} + C$
Therefore, this is the required answer.
Note:
In calculus, integration by substitution, also known as u-substitution or change of variables, is a method which is used for evaluating integrals or anti-derivatives. It is the counterpart to the chain rule for differentiation, in fact, it can also be considered as doing the chain rule "backwards". Also, there is another method which is known as integration by parts which is a process of finding the integral of a product of functions in terms of the integral of the product of their derivative and antiderivative. But, clearly, in this question, we didn’t have any product of functions thus, we cannot use the by parts method.
Here, we will first rationalize the given numerator and try to simplify it further so that we can apply the u-substitution method. Solving this further and using the formula of integration of ${x^n}$, we will be able to find the required answer. Integration is defined as the summation of all the discrete data.
Formula Used:
We will use the following formulas:
1) $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$
2) ${\sin ^2}x + {\cos ^2}x = 1$
3) $\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}}} + C$
Complete step by step solution:
The given integral function is $\int {\left( {\dfrac{{\sqrt {1 - \cos x} }}{2}} \right)} dx$.
This can also be written as: $\dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx$
Now, we will do the rationalization by multiplying and dividing by $\sqrt {1 + \cos x} $
Hence, we get,
$\dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {1 - \cos x} \times \sqrt {1 + \cos x} }}{{\sqrt {1 + \cos x} }}} dx$
Using the identity $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$ in the numerator, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {1 - {{\cos }^2}x} }}{{\sqrt {1 + \cos x} }}} dx$
Also, ${\sin ^2}x + {\cos ^2}x = 1$
Or $1 - {\cos ^2}x = {\sin ^2}x$
Thus, substituting this value in the numerator,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = \dfrac{1}{2}\int {\dfrac{{\sqrt {{{\sin }^2}x} }}{{\sqrt {1 + \cos x} }}} dx = \dfrac{1}{2}\int {\dfrac{{\sin x}}{{\sqrt {1 + \cos x} }}} dx$…………………..$\left( 1 \right)$
Now, by u-substitution, let $1 + \cos x = t$
Differentiating both sides, with respect to $x$, we get,
$ - \sin xdx = dt$
Or $\sin xdx = - dt$
Substituting this in $\left( 1 \right)$, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\int {\dfrac{1}{{\sqrt t }}} dt$
This can also be written as:
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\int {{t^{ - \dfrac{1}{2}}}} dt$
We know that, $\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}}} + C$
Hence, we get,
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - \dfrac{1}{2}\left( {\dfrac{{{t^{ - \dfrac{1}{2} + 1}}}}{{ - \dfrac{1}{2} + 1}}} \right) + C = - \dfrac{1}{2}\left( {\dfrac{{{t^{\dfrac{1}{2}}}}}{{\dfrac{1}{2}}}} \right) + C$
$ \Rightarrow \dfrac{1}{2}\int {\sqrt {1 - \cos x} } dx = - 2 \times \dfrac{1}{2}\left( {{t^{\dfrac{1}{2}}}} \right) + C = - \sqrt t + C$
But we know that, $1 + \cos x = t$
Hence,
$\int {\left( {\dfrac{{\sqrt {1 - \cos x} }}{2}} \right)} dx = - \sqrt {1 + \cos x} + C$
Therefore, this is the required answer.
Note:
In calculus, integration by substitution, also known as u-substitution or change of variables, is a method which is used for evaluating integrals or anti-derivatives. It is the counterpart to the chain rule for differentiation, in fact, it can also be considered as doing the chain rule "backwards". Also, there is another method which is known as integration by parts which is a process of finding the integral of a product of functions in terms of the integral of the product of their derivative and antiderivative. But, clearly, in this question, we didn’t have any product of functions thus, we cannot use the by parts method.
Recently Updated Pages
Fill in the blanks with suitable prepositions Break class 10 english CBSE
Fill in the blanks with suitable articles Tribune is class 10 english CBSE
Rearrange the following words and phrases to form a class 10 english CBSE
Select the opposite of the given word Permit aGive class 10 english CBSE
Fill in the blank with the most appropriate option class 10 english CBSE
Some places have oneline notices Which option is a class 10 english CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
When was Karauli Praja Mandal established 11934 21936 class 10 social science CBSE
Which are the Top 10 Largest Countries of the World?
What is the definite integral of zero a constant b class 12 maths CBSE
Why is steel more elastic than rubber class 11 physics CBSE
Distinguish between the following Ferrous and nonferrous class 9 social science CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE